Implementation of Hospital Management Information Systems: Obstacles and Challenges (Case Study at Santo Antonio Baturaja Hospital) - Sumiyem, Sr. M. Karla; Hartayu, TB. Titien Siwi (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
The Hospital Information System (HIS) handles and integrates the entire flow of hospital services. This study aimed to identify factors that affect the effectiveness and efficiency of HIS implementation and select strategies that can be used to overcome the inhibiting factors. In-depth interviews were used in this study with a qualitative and case-study strategy. The respondents were 26 officers selected by non-random purposive sampling. Data analysis used triangulation of in-depth interviews, document observations, and observations of HIS implementation. Data were transcribed verbatim and analyzed thematically. The results showed that the positive behavior of officers, leadership support, and officer abilities supported the implementation of HIS. However, there are still obstacles due to the attitude of officers and management policies. From document observations, it was found that officers had incorrect input, doubled input, and forgotten input. Due to a lack of Standard Operating Procedures (SOPs) and guidelines for implementing HIS, observations on its deployment revealed inconsistent data input. The strategy suggested to deal with the barriers included designing monitoring programs, creating SOPs, conducting extensive socializing programs, and conducting training programs to enhance officers' soft skills. It is clear that Human Resources play a crucial role for the effectiveness of HIS implementation.